Challenges in Teaching Integrated-Listening Skill in the University - Adin Fauzi (Universitas Ahmad Dahlan, 2019)
This research describes challenges encountered by EFL instructor in teaching integrated-listening skill in the university. To deal with this issue, a qualitative approach notably a basic interpretive study was deployed as the research design. Conducted in a private university in Blitar, East Java, this study took 23 students enrolled in Advanced Listening course as the participants. The data were collected through observation, interview, and document analysis. The result revealed that EFL instructor experienced some challenges in teaching integrated-listening skill to university students. The challenges included difficulties in locating appropriate materials, the students’ low level of English proficiency, and the students’ problematic attitude. Those problems hindered the students’ ability in both speaking and writing activities as a follow-up to listening activity. Current gap in listening-related study is recognized, and suggestions for both practitioners and future researchers are proposed.